2020
DOI: 10.3390/su12218847
|View full text |Cite
|
Sign up to set email alerts
|

Viability of a Single-Stage Unsaturated-Saturated Granular Activated Carbon Biofilter for Greywater Treatment

Abstract: Compared with conventionally collected sewage, source-diverted greywater has a higher potential for on-site treatment and reuse due to its lower contaminant levels and large volume. A new design of granular activated carbon (GAC) biofilters was developed by incorporating unsaturated and saturated zones in a single stage to introduce an efficient, passive, and easy-to-operate technology for greywater on-site treatment at the household scale. The design was customized for its intended application considering var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
(94 reference statements)
1
7
0
Order By: Relevance
“…Thus, a further increase in HRT would be required to meet the recommended effluent quality for reuse. However, the results were quite expected based on the previous reports that aerobic biofilter would be effective for greywater treatment [10,17,44,45].…”
Section: Treatment Of Raw Greywatersupporting
confidence: 60%
See 2 more Smart Citations
“…Thus, a further increase in HRT would be required to meet the recommended effluent quality for reuse. However, the results were quite expected based on the previous reports that aerobic biofilter would be effective for greywater treatment [10,17,44,45].…”
Section: Treatment Of Raw Greywatersupporting
confidence: 60%
“…Interestingly, the GAC biofilter in this study showed effective greywater treatment at shorter HRTs as compared to the previous reports on different biofilter studies for greywater [10,17,44,45]. Based on an extensive literature review, biofilters studied for greywater were operated without any liquid recirculation [8,10,17].…”
Section: Treatment Of Raw Greywatermentioning
confidence: 65%
See 1 more Smart Citation
“…Various methods, including physical, chemical, biological, and their combined techniques, have been used to treat GW 1,7 . However, these approaches ignored the potential application of decentralized on-site reuse of GW 8 . Traditional aerobic biological treatment technologies can achieve efficient removal of organics and nitrogen 3 , but several shortcomings are still remained.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high porosity, large specific surface area and excellent adsorption property, granular activated carbon (GAC) is widely used as the filter media for biological filters in wastewater treatment 13 . In the GAC-based biofilters, GAC media can enable the attachment and growth of biofilm 8 ; as the "pollutants transfer station", GAC can also uptake and store various pollutants that supplying for microbial metabolism 14 , all of which maintain high activity and biochemical reaction rate in the biofilm. GAC biofilters can achieve the efficient removal of pollutants by multiple processes including GAC filtration, adsorption and catalysis 14 , as well as the biosorption and biodegradation in biofilm 15 .…”
Section: Introductionmentioning
confidence: 99%